2019
DOI: 10.1111/sjop.12584
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differentiated relationship between appearance and fitness‐related social anxiety and the risk of eating disorders and depression in young adults

Abstract: Appearance‐related social anxiety has been identified as a relevant risk factor in the development of eating disorders (ED) and depression in young adults. However, less is known about the role that fitness‐related social anxiety may play on the emergence of these two psychopathological conditions. The present study aimed to examine whether appearance/fitness social anxiety may independently contribute to explaining the increased risk of ED and depressive symptoms in young adults. A total of 545 undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…Sample Size N = 396. ED Measure: EAT-26 %Female = 100%, Age = 20.1 years, BMI = 23.2 kg/m 2 6 6 Alcaraz-Ibáñez (2019) [ 82 ] Spain Cross-sectional design. Sample Size N = 545.…”
Section: Resultsmentioning
confidence: 99%
“…Sample Size N = 396. ED Measure: EAT-26 %Female = 100%, Age = 20.1 years, BMI = 23.2 kg/m 2 6 6 Alcaraz-Ibáñez (2019) [ 82 ] Spain Cross-sectional design. Sample Size N = 545.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been suggested that considering social comparisons refers not only to physical appearance but, additionally, to behaviors with the potential to modify one's body (e.g., eating or exercise) may incrementally contribute to explain DE (Fitzsimmons‐Craft & Bardone‐Cone, 2014; Fitzsimmons‐Craft, Bardone‐Cone & Harney, 2012). The latter may also apply to SPA experiences, in this case, considering not only physical appearance‐related ones but also those that refer to other body features such as functionality (Alcaraz‐Ibáñez et al ., 2019). Finally, the sample examined in the present study comprised a convenience sample of non‐clinical emerging adults.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their increasing prevalence and associated socioeconomic burden, eating disorders are considered a public health concern worldwide (Crow, 2014; Samnaliev, Noh, Sonneville & Austin, 2015; Smink, Van Hoeken & Hoek, 2012). For instance, previous research conducted in Western countries (Alcaraz‐Ibáñez & Sicilia, 2020; Alcaraz‐Ibáñez, Sicilia & Paterna, 2019) has reported high percentages of risk for an eating disorder among emerging adults (i.e., those that, aged between 18 and 30 years, are transitioning from late adolescence to their late twenties; Arnett, Žukauskiene & Sugimura, 2014). A clear example of the latter is Spain, where risk figures of approximately 20% have been reported for this population Therefore, it is not surprising that a considerable amount of research has been devoted to explaining the aetiology of eating disorders in both their clinical and sub‐clinical forms (i.e., disordered eating, DE) (Farstad, McGeown & von Ranson, 2016; Lantz, Gaspar, DiTore, Piers & Schaumberg, 2018; Schaefer & Thompson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they see an image that is influenced and "modified" by personal perceptions of the perfect body. This distortion of body image plus body image dissatisfaction has been linked to eating disorders 9 . Although REB, are at a midpoint between "normal" eating behaviors and eating disorders, their presence reveals psychological features of the individual that presents them, because it is associated with problems of self-perceived image distortion, leading to low rates of body satisfaction and low self-esteem, which favors the execution of REB 1,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Body dissatisfaction is characterized by value judgments about one's own body, which often do not conform to reality. It is influenced by social and cultural factors, among which body aesthetic models are the most important 9 . Body dissatisfaction is considered a risk factor for the development of risky eating behaviors and an important factor in the origin and maintenance of eating disorders.…”
Section: Introductionmentioning
confidence: 99%